2014
DOI: 10.1177/0954411914547714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feet position on standing balance in patients with diabetes

Abstract: Feet displacement is recognized to be an important element in standing and is also linked to postural instability in elderly people with diabetes. This study investigates standing balance in diabetic patients in four asymmetric feet displacements. Quiet standing balance was investigated using the Biodex Balance System in 18 diabetic patients and compared with 18 control elderly subjects. The four standing conditions, namely, comfortable feet position, preferred feet position with a stance width of 17 cm and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
3
0
6
Order By: Relevance
“…The older participants with diabetes used biofeedback and reduced errors of foot trajectory adaptation. In line with previous research on foot displacement adaptation in older adults and stroke patients [10,27,[42][43][44][45], this study found that detailed, meaningful information about goal-task performance in each step improved the accuracy of foot displacement. Like other groups, the older diabetic group compared their real-time step length and MTC with presented targets and reduced errors in the steps.…”
Section: Discussionsupporting
confidence: 90%
“…The older participants with diabetes used biofeedback and reduced errors of foot trajectory adaptation. In line with previous research on foot displacement adaptation in older adults and stroke patients [10,27,[42][43][44][45], this study found that detailed, meaningful information about goal-task performance in each step improved the accuracy of foot displacement. Like other groups, the older diabetic group compared their real-time step length and MTC with presented targets and reduced errors in the steps.…”
Section: Discussionsupporting
confidence: 90%
“…The screening procedures produced results similar to previous observations (Mehdikhani et al, 2014) as well we observed how this protocol had a good impact on patients from all points of view analysed, integrating motor activity with clinical care, and confirming the positive impact of the exercise therapy in diabetic patients (Francia et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…In a bipedal stance, the feet are positioned according to a multitude of possible conditions, the main ones being: feet apart, feet together, semitandem, and full tandem ( Figure 1 ). The legs are generally straight (they can be also flexed if required for the protocol) and the feet either form an angle of 15–30° or are positioned parallel (e.g., [ 113 ]). The intermalleolar distance is usually 5 cm for an angle of 30° and 10–15 cm for an angle of 15° [ 61 , 113 ] and varies between 0 and 15–20 cm for quasi-parallel feet [ 114 ].…”
Section: Main Postural Conditionsmentioning
confidence: 99%
“…The legs are generally straight (they can be also flexed if required for the protocol) and the feet either form an angle of 15–30° or are positioned parallel (e.g., [ 113 ]). The intermalleolar distance is usually 5 cm for an angle of 30° and 10–15 cm for an angle of 15° [ 61 , 113 ] and varies between 0 and 15–20 cm for quasi-parallel feet [ 114 ]. In a monopedal stance, the supporting leg can be the dominant leg or the nondominant leg according to the aim of the postural test (the dominant leg is the one used for kicking a ball).…”
Section: Main Postural Conditionsmentioning
confidence: 99%